Diagnosis of production processes in a glasswork aiming at the optimization of its system - Madeira, Carolina Lordes; Davila, Deivid Marcelino; Xavier, Thiago Padovani (Brazilian Journal of Production Engineering, 2023)
The diagnosis of processes in a company can reveal how the operations are as a whole, being essential to reach the maturity of the processes. In this study, we sought to analyze the use of the Quality Management System by a glass factory, located in the city of Baixo Guandu - Espírito Santo, through observations, data collection and information carried out during technical diagnostic visits. In addition, this article has the objective of building a diagnosis of productive processes, in order to outline solutions for some institutional setbacks and carry out an internal audit. From these applications, it will be possible for the company to better perform the services offered, as well as to optimize its space and workflow. Furthermore, to indicate suggestions that would circumvent the problems encountered, the following models were used: 5W2H, SWOT matrix and Management Excellence Model. To this end, a survey of specific data about the organization was carried out, such as the construction of the layout and process flowchart, analysis of the ISO 9001 Standard and verification of the 5S Quality Management program. From the indicators studied, it was found that the company has an excellent organization of the workforce, adapting its processes to reduce costs and raw materials. However, it showed some disorganization with customer documentation and with the optimization of available spaces. To this end, it was indicated that changes should be made to reduce the costs of the production chain, improve the layout of the showcase and better organize the documentation.
Keywords: Quality management; diagnosis of production processes; internal audit; ISO 9001; 5S; 5W2H; SWOT; MEG